Pénibilité du travail en hôpital psychiatrique - Caroline Cintas (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of this article is to show that the difficult work of nursing staff in psychiatric hospitals is less the result of the dangerousness of patients than the perceived impossibility of doing quality work. Through interviews with the staff, we attempt to analyze the difficulties felt. We develop the idea that this difficulty is related to the worry caused by current organizational changes. This explanation of the difficulty is more like a culture clash that emphasizes the difference between the prescribed work and the actual work. The discussion allows us to consider the theoretical framework of psychopathology in order to understand the results obtained. It is therefore from a work organization standpoint that we identify the difficulties of nursing staff in psychiatry. We hypothesize that the impact of the changes studied in this psychiatric hospital is not specific to this sector; however, the changes have a stronger impact in work situations that have the potential of becoming violent. In fact, the psychiatric hospital context highlights the exacerbation of the identified organizational problems.